2010
DOI: 10.1093/chromsci/48.6.441
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-MS Analysis of Ethanol Extract of Corydalis yanhusuo and Simultaneous Determination of Eight Protoberberine Quaternary Alkaloids by HPLC-DAD

Abstract: An accurate and simple analysis method by high-performance liquid chromatography (HPLC)-electrospray tandem mass spectrometry (ESI-MS-MS) for the ethanol extract of Corydalis yanhusuo was established in this study. In this method, a C(18) column was used, and the mobile phase was water (0.2% acetic acid, 0.1% triethylamine, v/v)-acetonitrile (24:76, v/v). Under the optimal analysis conditions established in this study, eight protoberberine quaternary alkaloids in the ethanol extract of Corydalis yanhusuo were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…After, that the modern analytical techniques have facilitated the isolation of alkaloids from plants is making it very simple. The use of 0.2% acetic acid and methanol as a solvent system reduces the ionization, more symmetrical peak and provides compelling evidence for alkaloids in HPLC-MS. Cheng et al (2010) also observed the better efficiency, using acetonitrile instead of methanol. However, mixtures consisting only of water and acetonitrile were not sufficient to separate completely the components in the ethanol extract, and some peaks overlapped.…”
Section: Discussionmentioning
confidence: 83%
“…After, that the modern analytical techniques have facilitated the isolation of alkaloids from plants is making it very simple. The use of 0.2% acetic acid and methanol as a solvent system reduces the ionization, more symmetrical peak and provides compelling evidence for alkaloids in HPLC-MS. Cheng et al (2010) also observed the better efficiency, using acetonitrile instead of methanol. However, mixtures consisting only of water and acetonitrile were not sufficient to separate completely the components in the ethanol extract, and some peaks overlapped.…”
Section: Discussionmentioning
confidence: 83%
“…Because alkaloids are generally not volatile, few of them can be analyzed by GC-MS. LC-MS and LC-MS/MS are often used for the analysis of alkaloids (Cheng, Shi, Zhen, Sun, & Jin, 2010;Gardner & Pfister, 2009;Liao, Chang, Yin, Wang, & Meng, 2014). Chromatography-mass *These authors contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…Gas chromatography-mass spectrometry (GC-MS) and liquid chromatography-mass spectrometry (LC-MS/MS) are the most commonly developed analytical methods to determine alkaloids. Because alkaloids are generally not volatile, few of them can be analyzed by GC-MS. LC-MS and LC-MS/MS are often used for the analysis of alkaloids (Cheng, Shi, Zhen, Sun, & Jin, 2010;Gardner & Pfister, 2009;Liao, Chang, Yin, Wang, & Meng, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several analytical methods have been developed and used for the detection of analogous alkaloids in Corydalis yanhusuo, a plant from the same genus as that of C. decumbens, such as high-performance liquid chromatography (HPLC) [17][18][19][20], liquid chromatography-mass spectrometry (LC-MS) [21][22][23], capillary electrophoresis (CE) [24,25], and high-speed countercurrent chromatography (HSCCC) [26]. However, only a few quantificational studies of C. decumbens alkaloids have been published.…”
Section: Introductionmentioning
confidence: 99%